Concept mapping and students’ attitudes towards biology: Analysis of school location differences and attitude toward concept maps - Bizimana, Emmanuel; Sibomana, Aimable (American Journal of Creative Education, 2024)
Many secondary school students, especially those in rural settings do not view favorably biology subject. The predominant use of the teacher-centered approach is mostly cited as the determinant. This study, therefore, investigated the effect of Concept Mapping (CM) mapping on students’ attitudes based on school location and how students experienced the CM. The study used a quasi-experimental research with a pre-test and post-test control group design. The research sample consisted of 305 students from lower secondary schools. Data were collected using Biology Attitude and Attitude toward Concept Mapping Questionnaires and were analyzed using Analysis of Covariance, Multivariate Analysis of Variance, and Independent t-student test. The findings showed that the CM is more effective in fostering students' attitudes toward biology than the conventional methods of instruction. Students' attitudes towards biology when taught using the CM did not significantly differ between those in rural and urban areas. Students showed a positive attitude towards using CM as a learning tool regardless of school location. To enhance student attitudes toward biology, schools should integrate Concept Mapping (CM) into the curriculum and provide professional development for teachers to effectively implement this method. Resources and support should be allocated, especially to rural areas, to ensure equitable access to CM tools. Gathering and responding to student feedback will help refine the approach, while continuous assessment will track its effectiveness. Encouraging collaborative learning with CM can further engage students and improve their overall learning experience in biology and other science-related courses.